Sequential identification of a degradable phosphate glass scaffold for skeletal muscle regeneration. (22nd October 2012) - Shah, Rishma; Ready, Derren; Knowles, Jonathan C.; Hunt, Nigel P.; Lewis, Mark P.
Abstract Tissue engineering has the potential to overcome limitations associated with current management of skeletal muscle defects. This study aimed to sequentially identify a degradable phosphate glass scaffold for the restoration of muscle defects. A series of glass compositions were investigated for the potential to promote bacterial growth. Thereafter, the response of human craniofacial muscle‐derived cells was determined. Glass compositions containing Fe4‐ and 5 mol% did not promote greater Staphylococcus aureus and Staphylococcus epidermidis growth compared to the control (p > 0.05). Following confirmation of myogenicity, further studies assessed the biocompatibility of glasses containing Fe5 mol%. Cells seeded on collagen‐coated disks demonstrated comparable cellular metabolic activity to control. Upregulation of genes encoding for myogenic regulatory factors (MRFs) confirmed myofibre formation and there was expression of developmental MYH genes. The use of 3‐D aligned fibre scaffolds supported unidirectional cell alignment and upregulation of MRF and developmental MYH genes. Compared to the 2‐D disks, there was also expression of MYH2 and MYH7 genes, indicating further myofibre maturation on the 3‐D scaffolds and confirming the importance of key biophysical cues. Copyright © 2012 John Wiley & Sons, Ltd.